Kondisi Neonatus Anak Babi yang Dilahirkan oleh Induk yang Disuntik Gonadotropin Sebelum Pengawinan (THE NEONATE CONDITIONS OF PIGLETS BORN FROM SOW INJECTED WITH GONADOTROPIN PRIOR TO MATING) - Montolalu, Friska Mery; Esfandiari, Anita; Ekastuti, Damiana Rita; Manalu, Wasmen (Jurnal Veteriner; Vol 19 No 1 (2018)DO - 10.19087/jveteriner.2018.19.1.76, 2018)
Injections of sows with pregnant mare serum gonadotrophin (PMSG) and human chorionic gonadotrophin (hCG) prior to mating have been shown to improve endogenous secretions of pregnant hormones that improve and optimize the uterine environment and condition during pregnancy that eventually lead to give birth to superior piglets. This experiment was designed to study the effects of PMSG and hCG injections of sows prior to mating on prenatal growth as indicated by the conditions of the the neonate piglets. Thirty mature female Landrace pigs were divided into 2 groups i.e., 15 pigs were injected with PMSG and hCG prior to mating, and the other 15 pigs were injected with physiological NaCl solution as a control. Before mating, the estrus cycles of the experimental sows were synchronized by injecting prostaglandin two times with 14 days interval. The experimental pigs were injected with PMSG and hCG or 0.90% NaCl solution at the same time with the second prostaglandin injection and were further mated naturally. During pregnancy, the experimental sows were maintained with the normal management condition. The results showed that piglest born to sows injected with PMSG and hCG prior to mating had shorter and faster birth process with higher activities and survivals as compared to those born to control sows. Piglets born by sow that were injected with PMSG and hCG before mating had a more optimum birth weight accompanied by greater body length, limb height, and higher rear limb height. Piglest born to by sows that were injected with PMSG and hCG prior to mating showed superior conditions that would contribute to optimum and superior preweaning and postweaning growths until maturity.